Development and characterization of dual modality system using polymeric nanocarrier - Liew, Hui Ching (2016)
Theranostic micelles and polymeric nanocarrier-based drug delivery system are two fields that have shown significant commitment in cancer treatment. Co-delivery of therapeutic and diagnostic agent in polymeric micelles for combination of therapy and diagnosis able to detect cancer cell in early stage, increase killing effect and suppress multidrug resistance (MDS) for better therapeutic effectiveness. Biocompatible and biodegradable polymeric nanocarriers generally have higher stability, sustained and controllable drug-release profiles and higher loading capacity for hydrophobic (poorly water soluble) drugs. Therefore, the aim of this study is to develop a dual modality micellar system using D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) as nanocarrier for co-delivery of docetaxel as a model chemotherapeutic drug and coumarin-6 as a model fluorescence imaging agent for simultaneous cancer imaging and therapy in early stage. The theranostic micelles were prepared by solvent casting method and characterize for their particle size, drug loading, drug encapsulation efficiency and in vitro drug release profile. This dual modality micellar system was successfully developed with average particle size of 79.59 nm in diameter and drug loading up to 15.46 μg/mg (encapsulation efficiency of 78.99%) and 9.83 μg/mg (encapsulation efficiency of 36.20%) for docetaxel and coumarin-6 respectively. Besides, the in vitro drug release profile of the micelles revealed a desired sustained and controlled drug release manner for both docetaxel and coumarin-6. In conclusion, the micelles size obtained is in favourable range for passive targeting through enhanced permeability and retention (EPR) effect and the drug loading and encapsulation efficiency attained are adequate for therapy and diagnosis purposes on cancer cells. The sustained drug release also beneficial in lower drug administration. This dual modality system is taking great advantages for tumour imaging and inhibition of tumour growth which is very important for early cancer detection, thereby having efficiency therapy on cancer cells.